2017
DOI: 10.1038/leu.2017.192
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3 randomized placebo-controlled trial of darbepoetin alfa in patients with anemia and lower-risk myelodysplastic syndromes

Abstract: The use of darbepoetin alfa to treat anemia in patients with lower-risk myelodysplastic syndromes (MDS) was evaluated in a phase 3 trial. Eligible patients had low/intermediate-1 risk MDS, hemoglobin ⩽10 g/dl, low transfusion burden and serum erythropoietin (EPO) ⩽500 mU/ml. Patients were randomized 2:1 to receive 24 weeks of subcutaneous darbepoetin alfa 500 μg or placebo every 3 weeks (Q3W), followed by 48 weeks of open-label darbepoetin alfa. A total of 147 patients were randomized, with median hemoglobin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 30 publications
2
91
0
4
Order By: Relevance
“…Effects of erythropoiesis-stimulating agents on overall survival of IPSS low/INT-1 risk, transfusion independent myelodysplastic syndrome patients: a cohort study Clinical guidelines recommend the use of erythropoietin stimulating agents (ESAs) in lower risk anaemic myelodisplastic syndrome (MDS) patients [1][2][3][4] and two registration trials for ESAs have just been completed 5,6 . We conducted a retrospective study in MDS patients selected by the characteristics predictive of ESA response 7 , treated in common practice and enrolled in the Italian Network of regional MDS registries (ClinicalTrials.gov Identifier: NCT02808858)…”
mentioning
confidence: 99%
“…Effects of erythropoiesis-stimulating agents on overall survival of IPSS low/INT-1 risk, transfusion independent myelodysplastic syndrome patients: a cohort study Clinical guidelines recommend the use of erythropoietin stimulating agents (ESAs) in lower risk anaemic myelodisplastic syndrome (MDS) patients [1][2][3][4] and two registration trials for ESAs have just been completed 5,6 . We conducted a retrospective study in MDS patients selected by the characteristics predictive of ESA response 7 , treated in common practice and enrolled in the Italian Network of regional MDS registries (ClinicalTrials.gov Identifier: NCT02808858)…”
mentioning
confidence: 99%
“…Platzbecker et al () reported that darbepoetin alfa 500 μg every 3 weeks was significantly superior to placebo with regard to the proportion of patients achieving International Working Group (IWG) erythroid response at 24 weeks (14·7% vs. 0% for placebo [ P = 0·016] for IWG 2006 criteria [Tefferi et al , ] and 19% vs. 3% for placebo [ P ‐value not reported] for IWG 2000 criteria [Cheson et al , ]); the minor response rate was also higher for darbepoetin alfa (39% vs. 6% for placebo; P ‐value not reported) (Platzbecker et al , ). After 48‐week open‐label follow‐up treatment with darbepoetin alfa, those who continued to receive treatment exhibited a response rate of 26·4%, and those who had switched from initial placebo treatment had a response rate of 28·9% (IWG 2006 criteria) (Platzbecker et al , ). The response rate for darbepoetin alfa 60–240 μg/week was reportedly higher (58%; IWG 2000 criteria) in a dose‐finding study (no placebo group) after 16 weeks of treatment (Jang et al , ), which had a shorter duration of follow‐up (median, 316 days) than the study reported by Platzbecker et al ().…”
Section: Resultsmentioning
confidence: 99%
“…After 48‐week open‐label follow‐up treatment with darbepoetin alfa, those who continued to receive treatment exhibited a response rate of 26·4%, and those who had switched from initial placebo treatment had a response rate of 28·9% (IWG 2006 criteria) (Platzbecker et al , ). The response rate for darbepoetin alfa 60–240 μg/week was reportedly higher (58%; IWG 2000 criteria) in a dose‐finding study (no placebo group) after 16 weeks of treatment (Jang et al , ), which had a shorter duration of follow‐up (median, 316 days) than the study reported by Platzbecker et al ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations